To Support a Stronger Climate Movement, Focus Research on Building Collective Power - Han, Hahrie; Barnett-Loro, Carina (Frontiers in Communication, 2018)
Building public will to address the climate crisis requires more than shifting climate change opinion or engaging more people in activism. Despite growing activism, the climate movement still needs to do more to translate public action into the power needed to effect meaningful change. This article identifies the kinds of research questions that need to be answered to bridge the gap not only between opinion and action, but also between action and political power. We draw on discussions from a conference that brought social scientists together with climate advocates in the United States. At this conference, movement leaders argued that to better support building a robust climate movement, research should move beyond traditional public opinion, communications, messaging, and activism studies toward a greater focus on the strategic leadership and collective contexts that translate opinion and action into political power. This paper thus offers a framework for synthesizing research on movement-building that demonstrates ways to focus research on power, and emphasizes the importance of organizing collective contexts in addition to mobilizing individuals to action.